Injectable Drug Delivery System Based on In Situ Self‐Assembly of Liquid Star Polyethylene Glycol–Poly(lactic‐co‐glycolic acid). Issue 3 (6th January 2021) - Eylon, Bat-hen; Shagan, Alona; Shabtay-Orbach, Ayelet; Gross, Adi; Mizrahi, Boaz
Abstract : Particulate systems are widely used in biomedical applications, yet current systems are limited by their stability, complicated production processes, and the use of toxic excipients and cosolvents. Here, a new concept for an injectable nanocarrier system based on the in situ self‐assembled star polyethylene glycol (PEG)– poly(lactic‐ co ‐glycolic acid) (PLGA)/drug mixture is presented. The new injectable material is based on a neat (solvent‐free) liquid copolymer that self‐assembles after it is injected along with the drug to form a particulate delivery system. The nanocarriers' formation rate and encapsulation capabilities of hydrophobic drugs can be fine‐tuned by changing the molecular weight of the PLGA segment. Furthermore, the starPEG–PLGA‐based system demonstrates potential as a drug carrier for hydrophobic drugs and shows biocompatibility with cell line culture. Abstract : An injectable drug delivery system that self‐assembles in the body overcomes some of the major limitations of commonly available particulate systems: stability, low drug loading, and complex manufacturing processes. The structure motif is based on a neat (solvent‐free) star polyethylene glycol (PEG)– poly(lactic‐ co ‐glycolic acid) (PLGA) copolymer that can be fine‐tuned by changing the molecular weight of the PLGA segment.